Line x Tester analysis for yield and its related traits in rice (Oryza sativa I.) (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Bangladesh Journal of Plant Breeding and Genetics, Vol.22(2) December 2009 1-6